Automatic Generation of Visual-Textual Presentation Layout - Yang, Xuyong; Mei, Tao; Xu, Ying-Qing; Rui, Yong; Li, Shipeng (ACM Transactions on Multimedia Computing Communications and Applications (TOMM), 2016)
Visual-textual presentation layout (e.g., digital magazine cover, poster, Power Point slides, and any other rich media), which combines beautiful image and overlaid readable texts, can result in an eye candy touch to attract users' attention. The designing of visual-textual presentation layout is therefore becoming ubiquitous in both commercially printed publications and online digital magazines. However, handcrafting aesthetically compelling layouts still remains challenging for many small businesses and amateur users. This paper presents a system to automatically generate visual-textual presentation layouts by investigating a set of aesthetic design principles, through which an average user can easily create visually appealing layouts. The system is attributed with a set of topic-dependent layout templates, a computational framework integrating high-level aesthetic principles (in a top-down manner) and low-level image features (in a bottom-up manner). The layout templates, designed with prior knowledge from domain experts, define spatial layouts, semantic colors, harmonic color models, and font emotion and size constraints. We formulate the typography as an energy optimization problem by minimizing the cost of text intrusion, the utility of visual space, and the mismatch of information importance in perception and semantics, constrained by the automatically selected template, and further preserves color harmonization. We demonstrate that our designs achieve the best reading experience compared with the re-implementation of parts of existing state-of-the-art designs through a series of user studies.
2017 ACM TOMM Nicolas D. Georganas Best Paper Award